Traumatic degloving injuries: a prospective study to assess injury patterns, management, and outcomes at a single center in northern India - Divij Jayant; Atul Parashar; Ramesh Sharma (Journal of Trauma and Injury)
Purpose This study investigated the epidemiology, management, outcomes, and postoperative disabilities of degloving soft tissue injuries (DSTIs) treated at a tertiary care center in northern India. Methods A prospective study of patients with DSTIs was conducted over 15 months. The type of degloving injury, the mechanism of injury, and any associated injuries were analyzed using the World Health Organization Disability Assessment Schedule (WHODAS) 2.0 along with the management, outcomes, and disabilities at a 3-month follow-up. Results Among 75 patients with DSTIs, the average age was 27.5 years, 80.0% were male, and 76.0% had been injured in traffic accidents. The majority (93.3%) were open degloving injuries. Lower limbs were affected most often (62.7%), followed by upper limbs (32.0%). Fractures were the most commonly associated injuries (72.0%). Most patients required more than two procedures, including secondary debridement (41.3%), split skin grafting (80.0%), flap coverage (12.0%), or vacuum-assisted closure (24.0%), while five patients underwent conservative management for closed degloving injuries. Postoperative complications included surgical site infections (14.7%) and skin necrosis (10.7%). Two patients died due to septic shock and multiple organ dysfunction syndrome. The mean length of hospital stay was 11.5±8.1 days, with injuries affecting the lower limbs and perineum requiring longer hospital stays. The mean WHODAS 2.0 disability score at 3 months was 19. Most patients had mild disabilities. Time away from work depended largely upon the site and severity of the injury. Approximately 75% of patients resumed their previous job or study, 14% changed their job, and 8% stopped working completely due to residual disability. Conclusions DSTIs are common injuries in trauma and management is challenging. Although open DSTI are clinically evident at secondary survey, closed degloving injuries may be missed in the primary survey, necessitating a high index of suspicion, thorough clinical examination, and protocol-based management. Primary preventive strategies (e.g., road safety protocols, preplacement training, and proper protective equipment in industries) are also needed to reduce the incidence of these injuries.